2019
DOI: 10.1071/ah18019
|View full text |Cite
|
Sign up to set email alerts
|

Health literacy education for rural health professionals: shifting perspectives

Abstract: Health literacy is a major issue for improving health outcomes of clients. In rural Victoria, Australia, the Gippsland Health Literacy Project (GHLP) educated local health services staff about health literacy and provided tools and techniques for health literacy implementation in services. This paper reports the outcomes of this project. Participants' change in knowledge was measured through pre- and post-project surveys and interviews. Descriptive analysis of survey data and analysis of interviews using quali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 4 publications
1
16
0
Order By: Relevance
“…The systems lens proved beneficial to facilitate analysis of the data as continuous, without an endpoint. Past studies have taken a linear approach to OHL operationalization (Finlay et al, 2018), but the expert panel endorsed the usefulness of a systems lens to understand the implementation of OHL, without a set endpoint. The realist method was useful to analyze OHL as a tangible way of describing a complex system and is able to tackle nonlinear data in a way that other methods cannot (Shearn et al, 2017;Emmel et al, 2018;Dalkin et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The systems lens proved beneficial to facilitate analysis of the data as continuous, without an endpoint. Past studies have taken a linear approach to OHL operationalization (Finlay et al, 2018), but the expert panel endorsed the usefulness of a systems lens to understand the implementation of OHL, without a set endpoint. The realist method was useful to analyze OHL as a tangible way of describing a complex system and is able to tackle nonlinear data in a way that other methods cannot (Shearn et al, 2017;Emmel et al, 2018;Dalkin et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…As a system issue, it is prudent to take a system-based approach to understand the mechanisms and impact of OHL interventions (Australian Commission on Safety and Quality in Health Care, 2013;Naccarella et al, 2016). OHL interventions can be multifaceted and benefit from reference to a larger guiding framework or strategy (Finlay et al, 2018). Frameworks to operationalize OHL (Department of Health and Human Services, 2017, Dodson et al, 2014, Dewalt et al, 2010, Tennessee Charitable Care Network, 2017, Australian Commission on Safety and Quality in Health Care, 2014, Brach et al, 2012 outline what is required for an organization to become health literate, but there is little detail on the implementation process (Berkman et al, 2011;Koh et al, 2013b;Ross et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Those delivering health care services face increased stress and professional responsibilities due to the increased demand for health care that LHL levels produce. Research has shown that the turnover rate of health care providers is often high in areas with significant rates of LHL among community members [47]. In this study, we have estimated the extra economic cost of higher rates of staff turnover for nurses, allied health professionals, and other medical staff members (a category that includes staff not classified as nurses, doctors, or other specialists).…”
Section: Costs To the Health Care Systemmentioning
confidence: 99%
“…Published evaluations of interventions designed to improve organisational health literacy responsiveness are predominantly limited to tertiary care settings and/or metropolitan areas, so their applicability to rural healthcare contexts where NCD prevalence tends to be higher is uncertain [35,36,39,40]. Of the few studies that have been conducted in primary care settings, many are limited to community pharmacies, which represent only a limited spectrum of all primary healthcare organisations [41,42].…”
mentioning
confidence: 99%